Pendekatan Saintifik dengan Metode Gasing pada Pembelajaran Fisika - Yesi Purwari (JPGI (Jurnal Penelitian Guru Indonesia), 2020)
This action research aimed to determine the effect of Scientific Approach with Gasing Method in Physics Learning of class XII Mipa 3 SMAN 3 Solok Selatan. The type of research that has been used is classroom action research with two cycles. The data of physics learning outcomes were collected by learning achievement test and students learning activities were collected by observation sheet. The data were analyzed quantitatively and qualitatively. The results indicated that (1) the average score of learning outcomes was increased from 73,75 (cycle 1) becomes 80,31 (cycle 2); (2) the average score of students‘learning activities was increased from 66,25 (cycle 1) to 86,25 (cycle 2)